The Impact of Protease during Recovery from Viable but Non-Culturable (VBNC) State in Vibrio cholerae - Anusuya Debnath; Shin-ichi Miyoshi (Microorganisms, 2021)
Vibrio cholerae can survive cold stress by entering into a viable but non-culturable (VBNC) state, and resuscitation can be induced either by temperature upshift only or the addition of an anti-dormancy stimulant such as resuscitation-promoting factors (Rpfs) at suitable temperature. In this study, the role of proteinase K was analyzed as an Rpf in V. cholerae. A VBNC state was induced in V. cholerae AN59 in artificial seawater (ASW) media at 4 °C, and recovery could be achieved in filtered VBNC microcosm, called spent ASW media, merely by a temperature upshift to 37 °C. The resuscitation ability of spent ASW was further enhanced by the addition of proteinase K. The mode of action of proteinase K was investigated by comparing its effect on the growth of the VBNC and culturable state of V. cholerae in ASW and spent ASW media. The presence of proteinase K allowed culturable cells to grow faster in ASW by reducing the generation time. However, this effect of proteinase K was more pronounced in stressed VBNC cells. Moreover, proteinase K-supplemented spent ASW could also accelerate the transition of VBNC into recovered cells followed by rapid growth. Additionally, we found that dead bacterial cells were the substrate on which proteinase K acts to support high growth in spent ASW. So, the conclusion is that the proteinase K could efficiently promote the recovery and growth of dormant VBNC cells at higher temperatures by decreasing the duration of the initial lag phase required for transitioning from the VBNC to recovery state and increasing the growth rate of these recovered cells.